Hypoxia regulates CD9 expression and dissemination of B lymphoblasts. (December 2022) - Rouger-Gaudichon, Jérémie; Cousin, Elie; Jakobczyk, Hélène; Debaize, Lydie; Rio, Anne-Gaëlle; Forestier, Anne; Arnaud, Marie-Pierre; Villacreces, Arnaud; Praloran, Vincent; Jacamo, Rodrigo; Galibert, Marie-Dominique; Troadec, Marie-Bérengère; et al.
Abstract: Acute lymphoblastic leukemias (ALL) are the most frequent cancer in children and derive most often from B-cell precursors. Current survival rates roughly reach 90% at 10 years from diagnosis. However, 15–20% of children still relapse with a significant risk of death. Our previous work showed that the transmembrane protein CD9 plays a major role in lymphoblasts migration into sanctuary sites, especially in testis, through the activation of RAC1 signaling upon blasts stimulation with C-X-C chemokine ligand 12 (CXCL12). Here, we identified common factors shared by the bone marrow and extramedullary niches which could upregulate CD9 expression and function. We found that low oxygen levels enhance CD9 expression both at mRNA and protein levels. We further determined that Hypoxia Inducible Factor 1α (HIF1α), the master transcription factor involved in hypoxia response, binds directly CD9 promoter and induce CD9 transcription. We also showed that CD9 protein is crucial for leukemic cell adhesion and migration at low oxygen levels, possibly through its action on RAC1 signaling. Mouse xenograft experiments indicate that HIF1α signaling pathway promotes ALL cells engraftment in a CD9-dependent manner. The present work increments our understanding of CD9 implication in ALL pathogenesis. Highlights: Tetraspanin CD9 expression is regulated by low O2 . The Hypoxia Inducible Factor 1α (HIF1α) signaling pathway is directly involved. CD9-mediated migration and dissemination depends on the HIF1α signaling pathway.